2010
DOI: 10.1186/1472-6939-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Handling ethical, legal and social issues in birth cohort studies involving genetic research: responses from studies in six countries

Abstract: BackgroundResearch involving minors has been the subject of much ethical debate. The growing number of longitudinal, pediatric studies that involve genetic research present even more complex challenges to ensure appropriate protection of children and families as research participants. Long-term studies with a genetic component involve collection, retention and use of biological samples and personal information over many years. Cohort studies may be established to study specific conditions (e.g. autism, asthma)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 22 publications
0
55
0
Order By: Relevance
“…One could argue, however, that that this is not really blanket consent, as the specific context of these studies allow for frequent contact between researchers, children and parents, thereby, providing many opportunities to reconsent. 24 An interview-based study with professionals associated with pediatric biobanks has shown that they would prefer 'broad consent' , but also think that if the research takes a too big step away from the original protocols, ethics committees should decide whether re-consent is necessary. 7 These studies suggest a discrepancy between what is formally consented (which is fairly broad and includes any potential future research) and the actual practices researchers feel comfortable with.…”
Section: Broad Versus Specific Consent In Pediatric Biobanksmentioning
confidence: 99%
“…One could argue, however, that that this is not really blanket consent, as the specific context of these studies allow for frequent contact between researchers, children and parents, thereby, providing many opportunities to reconsent. 24 An interview-based study with professionals associated with pediatric biobanks has shown that they would prefer 'broad consent' , but also think that if the research takes a too big step away from the original protocols, ethics committees should decide whether re-consent is necessary. 7 These studies suggest a discrepancy between what is formally consented (which is fairly broad and includes any potential future research) and the actual practices researchers feel comfortable with.…”
Section: Broad Versus Specific Consent In Pediatric Biobanksmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] The importance of conducting ethically sound pediatric biobank research 29 and the rapid developments in this field stress the need to scrutinize the concept of assent in pediatric biobank research. 14,18 Here, we will provide a conceptual analysis of assent, discuss the different underlying ethical principles and its, in our opinion, most tenable interpretation in pediatric research. In addition, we will consider how it should be implemented in biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…12 With regard to the different types of pediatric biobanks, the prevailing view is that assent should be obtained when possible. 3,[13][14][15][16][17][18][19] However, though many emphasize the importance of assent, few explain how they understand the concept and few have elaborated on the underlying grounds of assent and its role in pediatric biobanks. 20 This is not surprising as no consensus exists about how assent should be interpreted and implemented in biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 One distinct challenge is related to a child's ability to make a decision with regard to participating in medical research and sharing the information. There has been much discussion about the validity of parental consent and/or child assent, 4-6 the most suitable age for accepting child consent, 7 child withdrawal, 2,6,8,9 and reconsent when a child reaches adulthood. 2 Questions also have been asked about the right to share a child's information and whether there is any difference between medical and genetic information in relation to confidentiality.…”
Section: Introductionmentioning
confidence: 99%